The Effect Of Rentability, Audit Opinion, And Management Change On Auditor Switching In Banking Companies - Komang Puja Astiti; I Ketut Suryanawa (Jurnal Ekonomi, 2024)
Based on Government Regulation Number 20 of 2015 concerning Public Accounting Practices which eliminates restrictions on the provision of audit services by Public Accounting Firms (KAP), but still maintains restrictions for Public Accountants (AP) for five consecutive financial years. However, after this regulation came into effect, there were still companies that changed auditors before the specified time, one of which was banking sector companies.This study aims to analyze and determine the effect of Rentability, audit opinion, and management changes on auditor switching. The population in this study was 15 banking companies with a total sample of 105 observations selected using the purposive sampling method. The data analysis technique uses descriptive statistical techniques and logistic regression analysis with the help of SPSS 26.0. The results showed that Rentability and management change had a positive effect, while audit opinion had no effect on auditor switching in banking companies listed on the Indonesia Stock Exchange. The Nagelkerke R Square test results of 0.458 which means that the variation of auditor switching can be significantly influenced by the variables of Rentability, audit opinion, and management change by 45.8%, while the remaining 54.2% is explained by other factors that are not explained in this research model.